Spatial variation in the amino acid profile of four macroinvertebrate taxa along a highly polluted river. (1st September 2021) - Shakya, Manisha; Silvester, Ewen; Rees, Gavin; Stitz, Leigh; Holland, Aleicia
Abstract: Acid mine drainage (AMD) is one of the major environmental problems impacting aquatic ecosystems globally. We studied changes in the community composition of macroinvertebrates and amino acid (AA) profiles of dominant taxa along an AMD contamination gradient within the Dee River, Queensland, Australia to understand how AMD can affect the biomolecular composition of macroinvertebrates. Taxa richness and community composition of macroinvertebrates changed widely along the AMD gradient with significantly lower taxa richness recorded at the polluted sites compared to upstream and downstream sites. The Dipteran families: Chironomidae and Ceratopogonidae, the Odonata family Gomphidae, and the Coleoptera family Dytiscidae were the only families found at all sampling sites and were used here for AA analysis. There were significant variations in the AA profiles among the studied taxa. The AA profile of each taxon also varied among upstream, polluted and downstream sites suggesting that contamination of a river system with acid mine drainage not only alters the overall macroinvertebrate community composition but also significantly influences the AA profile of organisms that are tolerant to AMD. This study highlights the potential of using AA profiling to study the response of aquatic organisms to contamination gradients such as those associated with AMD. Graphical abstract: Image 1 Highlights: River affected by acid mine drainage (AMD) from mine 30 years after closure. AMD altered community structure and amino acid (AA) profile of macroinvertebrates. Inter and Intra-specific variations in AA profiles were detected among four taxa. Strongest changes in AA profile were observed within the family Chironomidae . AA profiling offers a new tool for assessing the environmental impact of AMD. Abstract : Contamination of a river system with acid mine drainage not only alters the overall macroinvertebrate community composition but also significantly influences the amino acid profile of aquatic macroinvertebrates along the contamination gradient.